PENGARUH KECERDASAN EMOSIONAL (EQ) TERHADAP HASIL BELAJAR PAI PADA SISWA KELAS VIII SMP ISLAM ATTARBIYYAH TELAGASARI KARAWANG - Nursanti, Desi; Darmiyanti, Astuti; Hakim, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of emotional intelligence in the learning process. Emotional intelligence refers to an individual's ability to recognize, understand, manage, and control their own emotions as well as those of others. This ability is assumed to influence students' success in achieving optimal learning outcomes. Therefore, this study aimed to determine the level of emotional intelligence, the learning outcomes in Islamic Religious Education (PAI), and the effect of emotional intelligence on PAI learning outcomes among eighth-grade students of SMP Islam Attarbiyyah Telagasari Karawang.This research employed a quantitative method with a correlational approach. The sample consisted of 64 eighth-grade students. Data were collected through questionnaires to measure emotional intelligence and documentation of students' scores to obtain PAI learning outcome data. Data analysis was conducted using the normality test, linearity test, Pearson Product-Moment correlation, coefficient of determination, and simple linear regression with the assistance of SPSS software.The results showed that there was no significant effect of emotional intelligence on PAI learning outcomes. This finding was evidenced by the simple linear regression test, which produced a significance value of 0.100, higher than the significance level of 0.05 (0.100 > 0.05). Therefore, the alternative hypothesis (Ha) was rejected and the null hypothesis (H₀) was accepted. These findings indicate that emotional intelligence does not have a significant effect on PAI learning outcomes among eighth-grade students of SMP Islam Attarbiyyah Telagasari Karawang.